Study on fatigue crack propagation behavior of TA15 titanium alloy repaired by laser deposition repair. Issue 12 (26th September 2022) - Zhou, Song; An, Jinlan; Wang, Xiangming; Xie, Li‐yang; Xu, Xingyuan
Abstract: The fatigue crack propagation behavior of TA15 titanium alloy repaired by laser deposition was studied based on the service reliability of aviation parts repaired by laser deposition. Forged TA15 titanium alloy was repaired by two methods including body‐repairing and surface‐repairing. The results show that the fatigue crack propagation rate of the surface‐repairing specimens is lower than that of the wrought specimens, and the fatigue crack propagation rate of the wrought specimens is lower than that of the body‐repairing specimens. The fatigue crack propagation rate depends on microstructure. In the surface‐repairing specimen, the crack propagates simultaneously along bimodal, heat‐affected region and basket‐weave structure. The basket‐weave structure effectively impedes the crack to propagate, which leads to fatigue crack propagation rate decrease. The wrought TA15 titanium alloy is bimodal structure, and the crack propagates mainly along the boundary of primary α phase which leads to form long crack. And in the body‐repairing specimen, the crack propagates in heat‐affected region with low strength leading to high fatigue crack propagation rate.